Analisis Laporan Keuangan Segmentasi Pada Perusahaan PT Mayora Indah TBk - Aulia, Irma; Amelia Putri, Indah; Irmayanti, Lisa; Damayanti, Maharani Putri; Mawadatullaela, Mawadatullaela; Fahri, Muhamad; Agustiningsih, Wulandari (CV. Era Digital Nusantara, 2025)
This study aims to analyze segment financial report disclosures at PT Mayora Indah Tbk and its subsidiaries, as well as to measure the contribution of each segment to the company's total revenue and profit. The method used in this research is quantitative, utilizing secondary data from the segment financial reports of PT Mayora Indah Tbk and its subsidiaries for the years 2019–2023. The population in this study consists of all business segments reported by the company, while the sample includes packaged processed food, packaged processed beverage, and financial services segments. The results show that only the packaged processed food and beverage segments meet the 10% revenue, profit, and asset tests, while the financial services segment does not meet these criteria. For future research, it is recommended to further analyze segments that do not meet the PSAK No. 5 standards and to extend the period and scope of the study to understand long-term trends in segment disclosures.